Special Worship in the British Empire: From the Seventeenth to the Twentieth Centuries - Hardwick, Joseph (Studies in church history, 2018)
Across the British empire, public worship was important for sustaining a sense of community and connectedness. This was most evident in special acts of worship, when the peoples of imperial territories, and sometimes of the whole empire, were asked at times of crisis and celebration to join together in special days or prayers of petition or thanksgiving to God. These occasions, ordered by a variety of civil and ecclesiastical authorities, were an enduring feature of all colonial societies from the seventeenth to the mid-twentieth centuries. Although these special acts of worship have considerable potential for deepening our understanding of various themes in the history of the British empire, they have yet to receive sustained analysis from scholars. This article is concerned with the fundamental task of considering why and how special prayers and days of fasting, humiliation, intercession and thanksgiving were appointed across the empire. By focusing on the causes of, and orders for, these occasions, it indicates reasons for the longevity of this practice, as well as its varied and changing purposes.